Development and Validation of a Gamification-Based Mathematics Curriculum for Senior High School - Molano, Raymund R (ASEAN Multidisciplinary Research Journal, 2022)
The purpose of this study was to develop as well as to determine the acceptability and the effectiveness of a Gamification-Based Mathematics Curriculum for Senior High School students with the end in view of upscaling their critical, analytical, and creative thinking skills geared towards improved mathematical competence and performance. A combination of descriptive-developmental and true experimental design was employed in this study. The participants in this study were consists of seven master teachers, five experts in the field of curriculum development and mathematics education, and eighty Grade 11 learners who are enrolled in General Mathematics for the School Year 2021-2022 under the online distance learning. Formal structured interviews, survey questionnaire and achievement test were used as research instruments. The researcher used thematic analysis, weighted mean, and t-test to analyze and interpret the gathered data in the study. Moreover, all statistical computations in this study were done using the Statistical Package for Social Sciences (SPSS). The findings of the of the study revealed that the expert-participants of the study assessed the Gamification-Based Student Portfolio and lesson plans as highly acceptable. Also, the experiment conducted revealed that there is a significant difference between the posttest scores and gain scores of the control and experimental groups in General Mathematics. Moreover, there is a significant difference between the pretest and posttest scores of the experimental group in General Mathematics.